2013
DOI: 10.1007/s11307-013-0656-5
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-Induced Errors in Tumor Quantification and Delineation in CT Attenuation-Corrected PET Images: Effects of Tumor Size, Tumor Location, and Respiratory Trace: A Simulation Study Using the 4D XCAT Phantom

Abstract: The respiratory motion-induced errors in tumor quantification and delineation are highly dependent upon the motion amplitude, tumor location, tumor size, and choice of the attenuation map for PET image attenuation correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…However, respiratory motion still is a largely neglected issue in clinical SPECT, in contrast to PET and preclinical SPECT . Quantitative images acquired without respiratory motion correction can potentially lead to inaccuracies in the estimated activity and consequently in the absorbed dose estimates …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, respiratory motion still is a largely neglected issue in clinical SPECT, in contrast to PET and preclinical SPECT . Quantitative images acquired without respiratory motion correction can potentially lead to inaccuracies in the estimated activity and consequently in the absorbed dose estimates …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Quantitative images acquired without respiratory motion correction can potentially lead to inaccuracies in the estimated activity and consequently in the absorbed dose estimates. [6][7][8] Respiratory motion compensation in PET has received substantial attention in the literature [9][10][11][12][13] with applications in specific thoracic areas like the lungs, 9,11 the heart 14,15 and more generic approaches. 12,[16][17][18] In SPECT, respiratory motion compensation techniques are largely focused on myocardial imaging, [19][20][21][22] which is still its major application area.…”
Section: Introductionmentioning
confidence: 99%
“…Final reconstructed PET images are degraded in two different ways as a consequence of respiratory motion: (a) Respiration causes lesion smearing, image blurring and quality degradation in PET images, and errors in the quantification of FDG uptake; and (b) The mismatch between PET and CT images results in incorrect AC and induces artifacts in the attenuation‐corrected PET images …”
Section: Introductionmentioning
confidence: 99%
“…The same group reported variation in tumor uptake during different respiratory phases due to the misregistration of PET and CT, and inaccurate attenuation correction in certain phases (Erdi et al ., 2004). Simulation studies have showed that respiratory motion-induced errors in tumor quantification and delineation highly depend on motion amplitude, tumor location, background activity and tumor size, with a 129% overestimation of volume for small liver tumors (Geramifar et al ., 2013; Park et al ., 2008). Severe artifacts have been reported for lesions near the lung base, where motion is more pronounced due to breathing (Cohade et al ., 2003; Geramifar et al ., 2013; Osman et al ., 2003; Park et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%